PATTERNS OF INDONESIAN-ENGLISH CODE-SWITCHING IN BROADCAST MEDIA: EVIDENCE FROM NET TV BREAKOUT - Abdurrahman Shaleh Reliubun (CV Sentra Nusa Connection, 2026)
This study examines patterns of Indonesian-English code-switching in selected episodes of NET TV BREAKOUT. Using a descriptive qualitative approach supported by frequency analysis, 54 code-switching occurrences were identified and classified based on their structural characteristics. The findings revealed four types of code-switching: intra-sentential, inter-sentential, tag, and intra-lexical switching. Intra-sentential switching was the most frequent type, accounting for 59.26% of the occurrences, followed by inter-sentential (18.52%), tag (14.81%), and intra-lexical switching (7.41%). Linguistically, switching occurred through lexical items, phrases, clauses, discourse markers, and morphologically integrated forms. The findings indicate that Indonesian remained the principal language of interaction, while English was predominantly incorporated within Indonesian linguistic structures. This study provides further evidence of patterned bilingual language use in Indonesian television entertainment discourse.